2015
DOI: 10.1016/j.ijsu.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Survival impact of cytoreduction to microscopic disease for advanced stage cancer of the uterine corpus: A retrospective cohort study

Abstract: Cytoreductive surgery to R0 is associated with improved OS in advanced uterine cancer. This effect is uniform among histologies. There is no interaction between histologic subtype and feasibility of complete cytoreduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Despite a few exceptions, 6 , 46 in our series, compared with most published series analyzing data for CRS alone in treating advanced or recurrent EC, 37 , 38 , 41 , 42 the only independent prognostic factor able to predict outcome was the completeness of cytoreduction. Although it remains conjectural whether HIPEC improved outcome in our series, an outcome finding that emerged from analysis of the 24 patients who had recurrent disease was the site of recurrence.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Despite a few exceptions, 6 , 46 in our series, compared with most published series analyzing data for CRS alone in treating advanced or recurrent EC, 37 , 38 , 41 , 42 the only independent prognostic factor able to predict outcome was the completeness of cytoreduction. Although it remains conjectural whether HIPEC improved outcome in our series, an outcome finding that emerged from analysis of the 24 patients who had recurrent disease was the site of recurrence.…”
Section: Discussioncontrasting
confidence: 56%
“…Bias apart, our outcome results compare well with published data, especially for those patients in whom CRS combined with HIPEC achieved complete cytoreduction. 12 , 37 , 38 , 41 , 42 , 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with type I endometrial cancer and no residual disease reported a median survival of 36 months, while those with incomplete debulking reported a median survival of 21 months; in the meantime, patients with type II endometrial cancer -the serous subtype-reported a median overall survival of 22 months when complete cytoreduction was performed and only 12 months for incompletely debulked patients. Moreover, the authors demonstrated that patients submitted to surgery after 2000 benefited more often from radical procedures and experienced a better outcome when compared to those submitted to surgery before 2000 (12). The strength of the study was related to the demonstration of the benefits of debulking surgery for type II endometrial tumors; the authors clearly demonstrated that type II tumors can be also submitted to debulking surgery with good results in terms of survival.…”
Section: Discussionmentioning
confidence: 94%
“…Another study conducted on the survival impact of cytoreduction for advanced-stage endometrial cancer comes from Alagkiozidis et al (12) patients submitted to debulking surgery for advanced-stage endometrial cancer between 1984-2009, with 105 of them being submitted to complete cytoreduction. Among cases in which suboptimally debulking surgery was performed, the most common sites of residual disease included the pelvic area (in 61% of cases), mid-abdomen (in 35% of cases) and upper abdomen (in 35% of cases).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies evaluated the impact of cytoreduction on survival for advanced-stage or disseminated peritoneal lesions of endometrial cancer. They showed that survival was significantly correlated with the presence of residual disease [33,34]. However, the definition of complete cytoreduction varied across studies.…”
Section: Discussionmentioning
confidence: 99%